The Effect of Preoperative Gender-Affirming Hormone Therapy Use on Perioperative Adverse Events in Transmasculine Individuals Undergoing Masculinizing Chest Surgery for Gender Affirmation. (13th April 2022) - Wu, Shannon S; Raymer, Charles A; Kaufman, Bram R; Isakov, Raymond; Ferrando, Cecile A
Abstract: Background: Many providers require cessation of gender-affirming hormone therapy (GAHT) for transgender patients prior to undergoing masculinizing chest surgery (MCS) due to concerns about increased adverse events in the presence of exogenous hormones. Evidence has suggested that continuation of GAHT for certain patients may be safe for gender-affirming procedures. Objectives: The aim of this study was to compare adverse event rates for GAHT cessation vs GAHT continuation in patients undergoing MCS. Methods: This multicenter, retrospective study included patients at the Cleveland Clinic and MetroHealth System who underwent MCS between 2016 and 2020. Results: There were 236 patients who met the inclusion criteria. Of these, 172 (72.9%) discontinued testosterone GAHT prior to surgery and 64 (27.1%) continued the therapy. Mean [standard deviation] age at surgery was 25 [8] years, and mean BMI was 29.5 [6.6] kg/m. 2 The median duration of testosterone therapy was 18 months (range, 0-300 months). There was no significant difference in tobacco use ( P = 0.73), diabetes ( P = 0.54), thrombophilia ( P = 0.97), or history of thromboembolism ( P = 0.39). Most patients underwent the double-incision free nipple graft technique (77.9%). There was no significant difference in surgical time ( P = 0.12), intraoperative complications ( P = 0.54), or postoperative complications ( P = 0.34). The most common complication was postoperative bleeding/hematoma (7.2%). Other complications included seroma (2.1%), infection (1.3%), and nipple graft failure (0.4%). There were no thromboembolic complications. Conclusions: There is no significant difference in the incidence of perioperative adverse events for patients who continue GAHT preoperatively vs patients who stop GAHT prior to MCS. Level of Evidence: 4: